Question
upstudy study bank question image url

8) Find \( f^{\prime}(x) \) using the limit definition of the denivative Then evaluate at \( x=-2 \). \[ f(x)=-6 x^{2}-3 x+2 \]

Ask by Alexander Reeves. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( f(x) = -6x^{2} - 3x + 2 \) is \( f'(x) = -12x - 3 \). When evaluated at \( x = -2 \), \( f'(-2) = 21 \).

Solution

To find f '(x) using the limit definition of the derivative, we recall that   f '(x) = limₕ→0 [(f(x + h) - f(x)) / h]. Given the function f(x) = -6x² - 3x + 2: 1. First, compute f(x + h):   f(x + h) = -6(x + h)² - 3(x + h) + 2.   Expand (x + h)²:    (x + h)² = x² + 2xh + h².   Thus:    f(x + h) = -6(x² + 2xh + h²) - 3x - 3h + 2          = -6x² - 12xh - 6h² - 3x - 3h + 2. 2. Find the difference f(x + h) - f(x):   f(x + h) - f(x) = [-6x² - 12xh - 6h² - 3x - 3h + 2] - (-6x² - 3x + 2)            = -12xh - 6h² - 3h. 3. Factor h from the numerator:   f(x + h) - f(x) = h(-12x - 6h - 3). 4. Divide by h to form the difference quotient:   [f(x + h) - f(x)]/h = -12x - 6h - 3. 5. Take the limit as h → 0:   f '(x) = limₕ→0 (-12x - 6h - 3)        = -12x - 3. Now, evaluate f '(x) at x = -2:   f '(-2) = -12(-2) - 3       = 24 - 3       = 21. Therefore, the derivative of the function is f '(x) = -12x - 3, and at x = -2, the derivative is 21.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find \( f^{\prime}(x) \) using the limit definition of the derivative, we start with the formula: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} \] For our function \( f(x) = -6x^2 - 3x + 2 \), we first compute \( f(x + h) \): \[ f(x + h) = -6(x + h)^2 - 3(x + h) + 2 \] Expanding \( f(x + h) \): \[ = -6(x^2 + 2xh + h^2) - 3x - 3h + 2 = -6x^2 - 12xh - 6h^2 - 3x - 3h + 2 \] Now, we find \( f(x + h) - f(x) \): \[ f(x + h) - f(x) = (-6x^2 - 12xh - 6h^2 - 3x - 3h + 2) - (-6x^2 - 3x + 2) = -12xh - 6h^2 - 3h \] Next, we substitute this back into the limit definition: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{-12xh - 6h^2 - 3h}{h} = \lim_{h \to 0} (-12x - 6h - 3) \] As \( h \) approaches 0, the limit simplifies to: \[ f^{\prime}(x) = -12x - 3 \] Now, we evaluate at \( x = -2 \): \[ f^{\prime}(-2) = -12(-2) - 3 = 24 - 3 = 21 \] Thus, \( f^{\prime}(-2) = 21 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy